Nonlinear equations arising in deferred correction of initial value problems - Daniel, James W. (1968)
Nonlinear equations arising in the deferred correction method for initial value problems are related to advanced multi-step methods. Such methods are shown to be stable in the usual norm if the usual condition of stability for the approximation to the highest order differential term is satisfied. (Author).
Keywords: MULTISTEP METHODS; (Boundary value problems; Approximation(mathematics); Differential equations; Iterations; Mapping(transformations); Nonlinear systems; Numerical methods and procedures); Operators(mathematics); Theorems; Theoretical Mathematics; Vector spaces